Making peace with referendums : Cyprus and Northern Ireland - Amaral, Joana (Syracuse studies on peace and conflict resolution., 2019)
"This manuscript presents the first in-depth comparative study of peace referendums, demonstrating that the way peace negotiations are conducted has an impact on referendum outcomes. Specifically, Amaral compares the Annan Plan negotiations in Cyprus and the Good Friday Agreement (GFA) negotiations in Northern Ireland. The underlying aim is to uncover how peace negotiations can favor broad support for peace settlements and potentially avoid a failed referendum"--